Inflation, inflation uncertainty, and growth: Evidence from Ghana - Nor Anis Shafai; Annuar Md. Nassir; Fakarudin Kamarudin; Norhuda Abdul Rahim; Nor Hayati Ahmad (Contemporary Economics, 2019)
Inflation and inflation uncertainty are critical factors influencing the functioning of markets and thus the efficient flow of economic activities. In this study, we investigated the effects of inflation and inflation uncertainty on growth in Ghana. Unlike the majority of the previous studies, we distinguished the short-run effects of inflation and inflation uncertainty on growth from the long-run effects. Also, unlike the previous studies, we examined whether increases in inflation uncertainty have the same effects on growth as decreases in it. By applying linear and nonlinear specifications to a data set covering the period 1963 to 2015, we found that inflation has both short and long-run negative effects on growth. Inflation uncertainty has a differential short-run effect and a negative long-run effect on growth. Increases in inflation uncertainty hurt growth, while decreases may reverse this pattern, albeit slowly. Both inflation and inflation uncertainty are critical determinants of growth in the country. To promote growth, policymakers should continue to pursue a low inflation target while ensuring minimal inflation uncertainty.
Keywords: E31; O47; O55; C22; 330; Inflation; Inflation Uncertainty; Growth; Ghana